2023
DOI: 10.1186/s40900-023-00464-z
|View full text |Cite
|
Sign up to set email alerts
|

Research involvement and engagement of adolescent and young adults in a cancer trajectory: a 5-year experience from a patient support facility at a university hospital

Abstract: Background The purpose of this case study is to describe how a vulnerable group of patients can be included in research. The activities, challenges, lessons learned, and reflections on the importance of patient involvement in research for 5 years (2016–2021) at the adolescent and young adult (AYA) cancer support facility, Kræftværket, are reported. Main body A patient panel at Kræftværket, the Youth Panel has multiple aims, one of which is the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We aligned with these three phases for the development of our proposed framework. For phase 1, identifying evidence to inform the methodological framework, aside from our experiences with the FUTURE Study, we drew from the aforementioned works by van Ham et al and Pappot et al on conducting patient engaged research with AYAs [11,12] to identify gaps and opportunities in AYA cancer patient engagement. Given the methodologic and content focus of the FUTURE Study, we also drew from Sherriff et al's 2014 work on considerations on conducting focus groups to evaluate sexual health service inter-ventions for young people [15].…”
Section: Research Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…We aligned with these three phases for the development of our proposed framework. For phase 1, identifying evidence to inform the methodological framework, aside from our experiences with the FUTURE Study, we drew from the aforementioned works by van Ham et al and Pappot et al on conducting patient engaged research with AYAs [11,12] to identify gaps and opportunities in AYA cancer patient engagement. Given the methodologic and content focus of the FUTURE Study, we also drew from Sherriff et al's 2014 work on considerations on conducting focus groups to evaluate sexual health service inter-ventions for young people [15].…”
Section: Research Contextmentioning
confidence: 99%
“…In their scoping review on patient engagement in Canada, Manafo et al found that when patients are engaged in research, there are improved research effectiveness and understanding of the community as well as increased enrolment and mobilisation of findings [16]. Patient engagement in cancer research has increased greatly over the last decade across many jurisdictions [3,5,12] and is of particular relevance for AYAs with lived experience of unique age-related challenges (e.g., sexual and reproductive health) [1,2,11,12].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation